Relationship of Basic Motor and Functional Abilities with Dribbling Speed in 10-17 Years Old Soccer Players - Matija Maršič; Branko Zupan; Rado Pišot; Mitja Gerževič (University of Maribor Press, 2016)
The aim of this study was to determine the relationship of selected motor and functional abilities with dribbling and changing direction with the ball in 183 young soccer players between 10 and 17 years of age (age 13,0 ± 1,8 years; body height 161,8 ± 13,3 cm; body mass 53,3 ± 14,7 kg). Based on the obtained data and results it was found that after the age of 13, in addition to other skills important for soccer game, it would be necessary to emphasise the elastic power of lower extremities and after the age of 16 additional emphasis should be put on high-speed and quality of execution of specific speed and agility type soccer movements. The most important ability related to dribbling and changing direction with the ball at the age 10-11 is agility. At the age 12-13 these are agility, aerobic-anaerobic endurance and relative elastic power of lower extremities, at the age 14-15 mainly aerobicanaerobic endurance and at the age 16-17, in addition to agility also acceleration and maximum running speed.